Do You Know Your Lines? - Rachapalli, Vamsidhar; Sharma, Pankaj; Kumar, Sheo; Uthappa, Mangerira Chinnappa (Journal of Clinical Interventional Radiology ISVIR, 2017)
The use of central venous catheters has become ubiquitous in the clinical practice. While a majority of them are easy to insert, many consider it a mundane interventional procedure. However, it is important to ensure that the right catheter is selected for the right patient. In addition, due diligence should be observed during site selection and catheter securement. This article briefly but concisely covers various aspects of venous catheter insertion ranging from catheter selection, patient preparation, choice of skin antisepsis to catheter tip position. This article, however, does not deal with the actual steps involved in the insertion of various catheters.
Keywords: venous; catheters; selection